(untitled) (Journal of the College of Basic Education, 2026)
The concept of disregard in Arabic phonetics is a method of explanation used by early scholars to explain certain changes in linguistic form. It represents an attempt to address potential violations of the linguistic rules they established to explain phonetic phenomena. Linguists considered certain sounds within the linguistic structure as disregarded, treating them as if they were not used in the linguistic form. This reveals that the concept of disregard originated from logical thought that permeated Arabic thought. Consequently, many phonetic issues based on the concept of disregard have been refuted by modern phonetics. Modern phonetics has demonstrated that disregard cannot provide a convincing explanation for many phonetic issues, necessitating the search for another cause. Therefore, this research, employing modern phonetics, seeks to find a convincing explanation for some phonetic phenomena that have undergone change.